Emotional creativity in the light of music education (Training and Practice : Journal of Educational Sciences, 2021)
The ongoing doctoral research at Benedek Elek Faculty of Pedagogy, Sopron University as well as the interactive preschool concerts held for 11 years by Camerata ART’issima (members: Krisztina Revesz Palfi, violin; Joseph Revesz, cello; Peter Kuzsner, piano), affecting about 120-130 kindergartens in the country, highlighted a very interesting area of the phenomenon of creativity, which has been identified and described as emotional creativity. The aim of the study is to explore the relationship between creativity and music and to illuminate the connections. Although the research is not yet complete and thus can be considered only as a kind of pilot program, it can be said that the results so far can form the basis of a new kind of music education concept that puts more emphasis on individual creativity, which, at the same time, considers the currently applied Kodály principles to a great extent as a base.